TAM of E-parking in order to Increase Regional Income - Yuliana Maulida; Muslim Al Kautsar; Abdullah Ramdhani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2021)
The phenomenon of e-parking itself has been implemented in several big cities in Indonesia, namely in Jakarta, Bali, Solo, Surabaya, and Bandung. The application of e-parking carried out by DISHUB in Bandung was used to overcome the problem of leakage of parking retribution receipts. This study aims examine Technology Acceptance Model (TAM) in the adoption of e-Parkir as parking infrastructure collection. In this study sampling using snowball sampling with staff in UPT Parkir Kota Bandung. The methodology of research is qualitative method and the data collected by interview, literature review, and observation. Meanwhile the analyses data done by reduction, presentation, and conclusion drawing and then the analyses method used description analysis. Conclude it was found perceived usefulness and perceived ease of use one of the most that affecting e-parkir acceptance. Our result also have confirmed perceived usefulness and perceived ease of use has been positively influencing attitude towards using e-parkir and give positive effect to behavioral intention dan actual usage e-parkir.